Effects of load magnitude, muscle length and velocity during eccentric chronic loading on the longitudinal growth of the vastus lateralis muscle - Sharifnezhad, A.; Marzilger, R.; Arampatzis, A. (The Journal of Experimental Biology, 2014)
The present study investigated the longitudinal growth of the vastus lateralis muscle using four eccentric exercise protocols with different mechanical stimuli by modifying the load magnitude, lengthening velocity and muscle length at which the load was applied. Thirty-one participants voluntarily participated in this study in two experimental and one control group. The first experimental group (N=10) exercised the knee extensors of one leg at 65% (low load magnitude) of the maximum isometric voluntary contraction (MVC) and the second leg at 100% MVC (high load magnitude) with 90 deg s-1 angular velocity, from 25 to 100 deg knee angle. The second experimental group (N=10) exercised one leg at 100% MVC, 90 deg s-1, from 25 to 65 deg knee angle (short muscle length). The other leg was exercised at 100% MVC, 240 deg s-1 angular velocity (high muscle lengthening velocity) from 25 to 100 deg. In the pre- and post-intervention measurements, we examined the fascicle length of the vastus lateralis at rest and the moment-angle relationship of the knee extensors. After 10 weeks of intervention, we found a significant increase (~14%) of vastus lateralis fascicle length compared with the control group, yet only in the leg that was exercised with high lengthening velocity. The findings provide evidence that not every eccentric loading causes an increase in fascicle length and that the lengthening velocity of the fascicles during the eccentric loading, particularly in the phase where the knee joint moment decreases (i.e. deactivation of the muscle), seems to be an important factor for longitudinal muscle growth.